HPV mRNA test in women with minor cervical lesions : experience of the University Hospital of North Norway - Sørbye, Sveinung Wergeland; Fismen, Silje; Gutteberg, Tore Jarl; Mortensen, Elin (Journal of Virological Methods, 2010)
In the Norwegian Cervical Cancer Screening Programme tests for detection of human papillomavirus (HPV) are used to triage women with minor cytological cervical lesions. The material in this study comprises samples from 1798 women in the period 2006–2008. The HPV test was performed according to the guidelines of the Norwegian Cancer Registry. The HPV mRNA test (PreTect HPV-Proofer) detects and types 5 high-risk genotypes (16, 18, 31, 33 and 45). The HPV mRNA results were compared to cytology and then biopsy up to December 2009. Women with minor cytological cervical lesions and negative HPV test were followed with a new PAP smear after 12 months. A total of 327 women (18%) were HPV mRNA positive. Of the 1798 women with minor cytological lesions, 232 women (13%) had moderate dysplasia, severe dysplasia or cancer and 144 women (8%) had severe dysplasia or cancer in biopsy. 57% of the women with a positive HPV mRNA test had moderate dysplasia, severe dysplasia or cancer. 37% had severe dysplasia or cancer. The sensitivity of the HPV mRNA test to detect moderate dysplasia, severe dysplasia or cancer was 81%. The specificity for moderate dysplasia, severe dysplasia or cancer was 91%. The negative predictive value (NPV) of the HPV mRNA test for moderate dysplasia, severe dysplasia or cancer was 97%. Of 11 women with cervical cancer, 10 were positive for HPV type 16 or 18. The HPV mRNA test seems more suitable than HPV DNA tests to triage women with minor cytological cervical lesions due to its higher specificity.